Building a recruitment database for asthma trials: a conceptual framework for the creation of the UK Database of Asthma Research Volunteers. Issue 1 (December 2016) - Nwaru, Bright; Soyiri, Ireneous; Simpson, Colin; Griffiths, Chris; Sheikh, Aziz
Abstract Background Randomised clinical trials are the 'gold standard' for evaluating the effectiveness of healthcare interventions. However, successful recruitment of participants remains a key challenge for many trialists. In this paper, we present a conceptual framework for creating a digital, population-based database for the recruitment of asthma patients into future asthma trials in the UK. Having set up the database, the goal is to then make it available to support investigators planning asthma clinical trials. Methods The UK Database of Asthma Research Volunteers will comprise a web-based front-end that interactively allows participant registration, and a back-end that houses the database containing participants' key relevant data. The database will be hosted and maintained at a secure server at the Asthma UK Centre for Applied Research based at The University of Edinburgh. Using a range of invitation strategies, key demographic and clinical data will be collected from those pre-consenting to consider participation in clinical trials. These data will, with consent, in due course, be linkable to other healthcare, social, economic, and genetic datasets. To use the database, asthma investigators will send their eligibility criteria for participant recruitment; eligible participants will then be informed about the new trial and asked if they wish to participate. A steering committee will oversee the running of the database, including approval of usage access. Novel communication strategies will be utilised to engage participants who are recruited into the database in order to avoid attrition as a result of waiting time to participation in a suitable trial, and to minimise the risk of their being approached when already enrolled in a trial. Results The value of this database will be whether it proves useful and usable to researchers in facilitating recruitment into clinical trials on asthma and whether patient privacy and data security are protected in meeting this aim. Conclusions Successful recruitment is fundamental to the success of a clinical trial. The UK Database of Asthma Research Volunteers, the first of its kind in the context of asthma, presents a novel approach to overcoming recruitment barriers and will facilitate the catalysing of important clinical trials on asthma in the UK.